Why don't families get along with eco-feedback technologies? A longitudinal inquiry - Barreto, Mary L.; Karapanos, Evangelos; Nunes, Nuno (My University, 2013)
Eco-feedback domestic technologies have gained momentum over the last decade. Yet, while a wide range of research prototypes and commercial products has been proposed, their acceptance by families is still limited. In this paper we report on our findings from interviews with 15 dual income families, during a year-long deployment of an eco-feedback technology that attempted to inquire into the factors that prohibited its adoption. We found the non-adoption of our system to be rooted in a number of systemic failures, relating to the physical context, the families' social dynamics and the roles assumed by family members, as well as families' priorities and the non-negotiability of their routines. Motivated by prior work and our empirical findings we propose three distinct dimensions but also phases in the adoption of eco-feedback technologies: orientation, incorporation and social integration, and discuss how these may hint at different barriers in the adoption of eco-feedback technologies.
Keywords: Eco-feedback technology; Families; Sustainability